2020
DOI: 10.1038/s42003-020-01265-w
|View full text |Cite
|
Sign up to set email alerts
|

Micromanipulation of prophase I chromosomes from mouse spermatocytes reveals high stiffness and gel-like chromatin organization

Abstract: Meiosis produces four haploid cells after two successive divisions in sexually reproducing organisms. A critical event during meiosis is construction of the synaptonemal complex (SC), a large, protein-based bridge that physically links homologous chromosomes. The SC facilitates meiotic recombination, chromosome compaction, and the eventual separation of homologous chromosomes at metaphase I. We present experiments directly measuring physical properties of captured mammalian meiotic prophase I chromosomes. Mous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 41 publications
(131 reference statements)
3
16
0
Order By: Relevance
“…However, the chromosome stiffness at different cell cycles have not been completely studied. In this project, we measured the chromosome stiffness of MEFs (Mouse Embryonic Fibroblasts) and found that the average Young's Modulus of MEF chromosomes was 340 ± 80 Pa (Figure 2B), which is consistent with our previously published data that MEF chromosomes have a modulus of 370 ± 70 Pa [13]. Next, we isolated chromosomes from mouse MI oocytes and measured their stiffness (Figure 2A).…”
Section: Chromosome Stiffness From MI Oocytes Is About 10 Times Highe...supporting
confidence: 87%
See 2 more Smart Citations
“…However, the chromosome stiffness at different cell cycles have not been completely studied. In this project, we measured the chromosome stiffness of MEFs (Mouse Embryonic Fibroblasts) and found that the average Young's Modulus of MEF chromosomes was 340 ± 80 Pa (Figure 2B), which is consistent with our previously published data that MEF chromosomes have a modulus of 370 ± 70 Pa [13]. Next, we isolated chromosomes from mouse MI oocytes and measured their stiffness (Figure 2A).…”
Section: Chromosome Stiffness From MI Oocytes Is About 10 Times Highe...supporting
confidence: 87%
“…We previously demonstrated that the central elements of the synaptonemal complex do not contribute to chromosome stiffness, and so we shifted our focus to the role meiotic cohesins during the meiosis I stage [13]. Cohesins can still load onto chromosomes even when an intact synaptonemal complex is not formed [31].…”
Section: Meiosis-specific Cohesins Do Not Contribute To Chromosome St...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the factors involved in MSCI are well established, the mechanisms that physically separate sex chromosomes from autosomes have been an open question in the field. Wang et al (2019) demonstrated there are more long-distance interactions within the X chromosome compared to autosomes, which may indicate X chromosomes are softer than stiff autosomes (Biggs et al, 2020). Unlike the rod-shaped autosomes, the territory of the X and Y chromosomes gradually becomes globe-shaped during sex-body formation.…”
Section: Introductionmentioning
confidence: 98%
“…This complexity is reflected in a dedicated meiotic structure called the synaptonemal complex (SC). This supramolecular protein structure binds together homologous chromosome pairs and is essential for the maturation of inter-homologue crossover recombination events, and thereby fertility 2 – 6 . Consequently, meiotic proteins responsible for this process are highly specialised and otherwise silenced in somatic cells.…”
Section: Introductionmentioning
confidence: 99%